2018
DOI: 10.1002/jbm.a.36553
|View full text |Cite
|
Sign up to set email alerts
|

Particulate and ion forms of cobalt–chromium challenged preosteoblasts promote osteoclastogenesis and osteolysis in a murine model of prosthesis failure

Abstract: This study investigated the interactive behavior of the particulate and ion forms of Cobalt-Chromium (Co-Cr) alloy challenged preosteoblasts during the process of prosthetic implant loosening. Preosteoblasts were challenged with Co-Cr particles or Co(II) ions for 72 hours, followed by the proliferation and PCR assays. For in vivo test, a titanium-pin was implanted into proximal tibia of SCID mice to mimic knee replacement. Co-Cr particles or Co(II) ion challenged preosteoblasts (5×105) were intra-articularly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…3). Genetics, lifestyles, allergies, preexisting ailments, acquired metal sensitivity and allergy, female gender, individuals with bilateral hip/knee implants, obesity, underweight, renal insufficiencies/failures, and highly physical jobs that require heavy lifting have all been implicated in the mechanism of metallosis [9,12,26,29].…”
Section: Postoperative Joint Loading and Fluid Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…3). Genetics, lifestyles, allergies, preexisting ailments, acquired metal sensitivity and allergy, female gender, individuals with bilateral hip/knee implants, obesity, underweight, renal insufficiencies/failures, and highly physical jobs that require heavy lifting have all been implicated in the mechanism of metallosis [9,12,26,29].…”
Section: Postoperative Joint Loading and Fluid Pressurementioning
confidence: 99%
“…However, wear particles alone can be recognized as antigens in certain instances [43]. The uptake of particulate metal debris by macrophages through phagocytosis is a key process by which implants may trigger inflammatory responses leading to metallosis [28,29,44]. After macrophages identify particles through pattern recognition receptors, including toll-like receptor, retinoid acid-inducible gene-1-like receptors, aim 2-like receptor, and nucleotide-binding oligomerization domain-like receptors, they form a cascade of reactions generating pro-inflammatory cytokines, including interleukin-1β, interleukin-6, interleukin-18, and tissue necrosis factor-α, as well as the chemokines (CXCL8, CCL2, and CCL3), and other small molecule inflammatory mediators [31,42].…”
Section: Macrophages and Pattern Recognition Cascadementioning
confidence: 99%
“…In addition, metal ions (Co ions) can regulate adhesion of inflammatory cells such as neutrophils to endothelial cells (Wagner et al, 1998). It has also been reported that the presence of CoCr particles resulted in greater inflammatory response (Yang et al, 2019). The dysregulation of endothelial cells and activation of inflammatory response could increase the expression of proinflammatory cytokines and active metalloproteinase, affecting the microenvironment around the corroded stents, possibly leading to the development of ISR.…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, CoCr particles in range of nanometer to micrometer have been used to investigate their effect on the various types of cells, for example, fibroblasts. It has been demonstrated that CoCr particles can not only lead to the DNA damage in human fibroblasts (Papageorgiou, Brown, et al, 2007; Papageorgiou, Yin, et al, 2007; Tsaousi et al, 2010), but also can interfere with the growth, maturation and function of preosteoblasts (Yang et al, 2019). It was reported that clinically relevant CoCr NPs caused significant changes in the structural integrity of the dura mater, which may lead to significant secondary effects, such as local nerve tissue inflammation (Papageorgiou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion involves the gradual destruction of materials by electrochemical reactions within their environment. , It is an exothermic process involving electrochemical degradation of metallic materials, propelled by the thermodynamics of a metal shift toward a low energy (chemical) potential, which usually takes place as an electron flows from the anodic region to the cathode . Corrosion occurs basically via three distinct stages of events: (1) Ions from the metal surface dissolve in oxidation in the electrochemical active surrounding releasing cations.…”
Section: Corrosion In Arthroplastymentioning
confidence: 99%